The Integration of Haisi Culture and Environmental Protection Concepts in Environmental Design: Education and Sustainability Path - Cai Tongxin; Zhang Jiawei (SHS Web of Conferences)
This study explores the integration and innovation of Haisi culture and environmental protection concepts in modern environmental design, especially in the application and practice of environmental design education. In the context of globalization and urbanization, environmental design not only carries cultural heritage, but also plays an important role in promoting social transformation and sustainable development. The qualities and spiritual connotations of cross-cultural art provide unique inspiration for environmental design, and the integration of ecological concepts highlights the dual value of design education and sustainable development. We examine the historical and artistic characteristics of Haisi culture, analyze its potential for application in contemporary design, and explore the reproduction of culture and ecosystems. By exploring the interdisciplinary and green design needs of environmental design education, we promote the integration of traditional culture and environmental concepts, cultivate designers with a sense of cultural responsibility and environmental awareness, support the sustainability of environmental design education, promote the sustainable development of environmental design, and provide an innovative teaching model for the reform of the education system.